2009
DOI: 10.1371/journal.pone.0004666
|View full text |Cite
|
Sign up to set email alerts
|

Crucial Role of the CB3-Region of Collagen IV in PARF-Induced Acute Rheumatic Fever

Abstract: Acute rheumatic fever (ARF) and rheumatic heart disease are serious autoimmune sequelae to infections with Streptococcus pyogenes. Streptococcal M-proteins have been implicated in ARF pathogenesis. Their interaction with collagen type IV (CIV) is a triggering step that induces generation of collagen-specific auto-antibodies. Electron microscopy of the protein complex between M-protein type 3 (M3-protein) and CIV identified two prominent binding sites of which one is situated in the CB3-region of CIV. In a radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
43
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 14 publications
(36 reference statements)
3
43
0
1
Order By: Relevance
“…In this situation, a spectrum of extracellular matrix targets is available for recognition by bacterial adhesins. In recent work, fibronectin, laminin, vitronectin, and collagens I and IV have been identified as such targets [7,8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…In this situation, a spectrum of extracellular matrix targets is available for recognition by bacterial adhesins. In recent work, fibronectin, laminin, vitronectin, and collagens I and IV have been identified as such targets [7,8,9,10,11,12,13]. …”
Section: Introductionmentioning
confidence: 99%
“…M proteins of certain emm types facilitate host adhesion by binding collagens (Dinkla et al, 2003;Nitsche et al, 2006), which are abundant structural proteins in the mammalian extracellular matrix (Bosman and Stamenkovic, 2003;Gelse et al, 2003). A sequence of 8 amino acids AXYLZZLN was found to be the collagen-binding motif of the M3 protein of S. pyogenes and the M protein FOG of S. equisimilis, and recent work shows that this motif enables these M proteins to bind the CB3-region of collagen IV (CIV) (Dinkla et al, 2009). This region is part of a triplehelical domain and bears a binding site for a1-and a2-integrins.…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent epidemiological studies in areas where ARF is common today have found that ARF is not restricted to these rheumatogenic strains (4), raising questions around the concept of rheumatogenicity and emm type. It has further been postulated that certain GAS emm types (most notably emm3) may be rheumatogenic due to the presence of a specific collagen-binding motif, designated peptide associated with rheumatic fever (PARF), which elicits an immune response to type IV collagen (5,6). To date, however, the presence of the PARF motif has not been systematically assessed in a large collection of GAS strains temporally associated with ARF.…”
mentioning
confidence: 99%